PROFESSIONAL ROLES OF A DANCE TEACHER AND THEIR ANALYSIS IN HIGHER EDUCATION - Jegere, Paula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Dance teachers fulfil different roles in their daily work. It reflects as a need to act according to the circumstances that appear as a part of work process. If the economic situation in a certain country is unstable then more professionals are urged to obtain additional knowledge to use skills necessary for the development and sustainability of the profession. Skills that are often provided by other specialists in a different field of work. First of all the roles that are fulfil in a daily work need to be acknowledged and supported – denial of these roles can influence professional work/activity. Then according to the financial status occurs roles of secondary meaning, not used in the daily professional activities but rather occasionally. The recognition of one’s professional roles and their variability may take place in the higher education study process, when students realize and are motivated to obtain more information and knowledge/skills to expand their professional work. The aim of this article is to analyse professional roles of students in different higher education dance programs. The aim is carried out in the analysis of literature and on it’s base promoted evaluation indicators and levels of professional roles realized by dance teachers. A questionnaire is designed on a basis of these indicators and levels and offered for approbation to students in higher education dance programs in Latvian Academy of Music, Liepaja University, Latvian Academy of Culture